The Study of Islamic Law About The Deceased Muslim and Its Cultural Symbols in Sumpur Kudus, West Sumatera, Indonsia - Salma, Salma (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
Every living thing dies. The death of a person leaves an obligation for the living to perform some rituals for the deceased. The rituals have been regulated in such a way according to Islamic Sharia (law). Nevertheless, the practices could not be separated from the local traditions and customs. Their influences can be seen through various symbols used in the rituals for the deceased, as found in Sumpur Kudus, West Sumatra. The community has been using many symbols in carrying out the various rituals for the dead, such as kain unduang-unduang (a kind of white cloth stretched above the grave), parian (a bamboo tree that is used as a water container), payuang panji (an umbrella protecting the dead body along the way to the grave) and daun sicerek (a plant used for fragrance). The people stated that, in general, these symbols contain a deep affection of the living towards the deceased. The type of the study was field research with a qualitative approach. The data was gathered by observation, in-depth interviews, and documentation study. The analysis was done descriptively by data reduction, display, and verification (drawing conclusion). The result showed that the Sumpur Kudus community is a Muslim community that does not ignore Islamic law in the organization of their deceased. These symbols serve as tools to show affection of the living towards the deceased. The symbols do not only serve as symbols of affection, but they are also laden with the belief that contain transcendental values.